O CENTROWEG em Jaraguá do Sul/SC: história e formação profissional do menor aprendiz - Mehanna, Salimi da Silva (2023)
This dissertation is related to the research line Society, Knowledge and Education of the Postgraduate Program in Education of the State University of Western Paraná, Francisco Beltrão Campus. Our object of study is the training of young apprentices at the CentroWEG, known as the “School of WEG”, located in the industrial park of the company WEG S. A. in Jaraguá do Sul/SC. WEG S. A. is one of the largest manufacturers of electronic devices in the world. In this text we try to explain part of the history of CentroWEG, how the process of training young people took place, what courses were/are offered, what the requirements were and how long the training lasted. The training center focused on qualifying the young trainees for the needs of the company, i.e. developing activities that required technical knowledge and/or the field of equipment used in the industrial processes. The main objective of the study is to understand the history and role of CentroWEG in the training of young apprentices. Therefore, a bibliographic research and a collection of documents were carried out to understand the training process of the young people. For this research, we conducted readings, image and document collections with a qualitative approach. It is therefore a bibliographic/documentary research with a qualitative approach. Due to the difficulties in accessing the CentroWEG archives caused by the COVID-19 pandemic, as well as the restrictions imposed by the management of the institution itself, we used photographic images from the WEG museum or from the Internet as our main research source, and we studied the institution as a historical source. Our reading was historically and theoretically oriented: Antonio Gramsci (1980, 2004), Demerval Saviani (1996, 2015), Gaudêncio Frigotto (1983, 2005), Maria Ciavatta (2005, 2022), among others, in search of the relationships between education, work, professional training and regional development, in order to contribute to research in the field of education and professional qualification. In this study, we have established that the ruling class controls both the field of education and the means of production, creating a dualism between social classes. Considering that the training of CentroWEG is fundamentally oriented to the demand of the market, especially of the company itself, we haveestablished that training is an arm of capital, which underlines that CentroWEG does not allow human/emancipatory training in the social and critical training process of workers.